Gestão do território e responsabilidade social das empresas de mineração no estado do Pará - MEDEIROS, Gláucia Rodrigues Nascimento (Universidade Federal do Pará, 2017)
In this article, we will try to introduce a research related to Social Responsibility Actions undertaken for the mining company Vale in the municipalities of Parauapebas and Canaã dos Carajás, because both as cities has the largest Mining Projects in Brazil, and Canaã soon will welcome the Major Mining Company the planet Called Ferro Carajás S11D project. The experienced changes in territories occur instantly, as the Municipal Government and Vale are organized to prepare a city to begin the Carajás S11D project, looking this time to invest in targeted infrastructures construction and refurbishment of public facilities, bringing many impacts positive results due to the acceleration of investments and activities in the region negative impact to create chaos, because the increase in volume migration, because the projects in the region are still working more for longer than 30 years of form interruptible that strengthens the migration people all states. The research territory Pará examines in measure the land management benefits of exploration of mining production activities resulting energy Projects large and aims to analyze how actions Vale company direct on improving the local population quality of life, analyzing also commitment and responsibility company related to in activity and decision making paragraph minimize negative impacts on society and the environment. The search also analyzes the relationship between the Government and the Company, as well as analyze a territoriality exercised paragraph controlling a through area of data released by the company Vale and Municipal Government related to investment in Social Responsibility Projects, a measure the quality in application resources for sustainable development.